Clinical presentation and protocol for management of hepatic sarcoidosis. (March 2015) - Modaresi Esfeh, Jamak; Culver, Daniel; Plesec, Thomas; John, Binu
<x xml:space="preserve">Abstract</x> The liver is one of the most commonly involved extrapulmonary sites in sarcoidosis. Hepatic sarcoidosis has a broad range of presentations from scattered, asymptomatic noncaseating granulomas with normal liver enzymes, which are very common in patients with known pulmonary sarcoidosis, to portal hypertension and cirrhosis, which are relatively uncommon. Diagnosis is based on a combination of clinical, laboratory and histological manifestations. The authors' protocol for management of patients with suspected sarcoidosis of the liver without focal lesions includes a transjugular liver biopsy with portal pressure measurements to confirm the diagnosis, rule out coexisting liver diseases and to identify select patients with fibrosis or portal hypertension for consideration of immunosuppression. Steroids and azathioprine are the preferred agents and methotrexate is not recommended.